Determinação das deformações limites de chap as metálicas anisotrópicas considerando o atrito no estiramento com punção - De Souza, Luis Henrique Batista; De Araújo Moreira Filho, Lindolfo; Menezes, Miguel Ângelo [UNESP] (My University, 2010)
This work aims at determining the influence of anisotropy of the material using the new Hill's quadratic and friction on the prediction of strain limits for using analysis of formability of sheet metal forming limit diagrams. For this, was developed a new theory to calculate the strain limits considering the anisotropy and friction. To verify the functionality of the theory provided the theoretical results were compared with experimental results obtained from the literature for several different materials. It was found that the theory predicts satisfactorily the mechanical behavior of various sheet metals. Nevertheless, the theory satisfactorily demonstrate the role of friction in the process and indicate that the anisotropy of sheet metal to increase the ability of deformation of the sheets, it is observed that the prediction is generally better to have that plate because of strains between the deformations main in the rolling direction for the directions transverse to the rolling direction than or equal to zero.
Determination of strain limits of anisotropic sheet metals considering the friction in punch stretching
Keywords: Anisotropy; Friction; Plastic instability; Sheet forming